Optimal control: From sensitivity improvement to alternative pulse-sequence design in solid-state NMR - Blahut, Jan; Tošner, Zdeněk (Solid state nuclear magnetic resonance, 2025)
Exciting developments in new experimental methods for multidimensional solid-state NMR spectroscopy have recently been achieved using optimal-control theory. These results, in turn, have triggered the development of new pulse sequences based on traditional analytical theories. This trend article summarises the key steps leading to these advancements. It also describes additional applications of optimal control beyond structural biology and envisions similar progress in the NMR of solid materials. Despite attractive features of optimal-control pulse sequences demonstrated in the proof-of-concept studies, their experimental utilization remains sparse, probably due to the lack of awareness among experimentalists. We hope this mini-review helps to spread optimal-control methods into routine experimental workflows. Furthermore, we offer a personal outlook on how numerical optimisations could in general enhance the experimental capabilities of solid-state NMR in the near future, with optimal control serving as a pioneer exploring new possibilities.